Composing in real-time? - Risset, Jean-Claude (Contemporary Music Review, 1999)
The author briefly describes his Duet for one pianist, which is probably the earliest instance of live interaction between performer and computer entirely within the realm of acoustic sounds. However the main point of the article is to draw attention upon problems related to real-time. Not only does the use of real-time systems bring limitations and difficulties for the durability of the music, but one may even argue that the concept of real-time concerns primarily performance and may be of little relevance to musical composition.